Operational research of ground heat pump and passive air conditioning - Paweł Gil; Rafał Gałek; Krzysztof Kiedrzyński; Adrian Kmieciński (Advances in Mechanical and Materials Engineering, 1970)
This article presents a passive air conditioning system using the lower source of the ground heat pump. Passive air conditioning uses the natural cold accumulated in the ground especially in the summer season. A hydraulic diagram and the principle of passive air conditioning were presented in the text. The purpose of the measurement was to determine the cooling power, the characteristic temperatures and the soil temperature distribution at the depth of 2 meters at the ground excavated site of the spiral ground heat exchanger. Annual temperature distributions in the ground which directly affect annular cooling power were presented. Advantages and disadvantages of passive air conditioning have also been presented.